Composite ceramic modified magnesia-carbon refractory and preparation method thereof
Patent Information
- Application Number
- CN202611242644.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-17
- Publication Date
- 2026-10-16
AI Technical Summary
[0005]针对现有传统镁碳耐火成型部件或耐火砖砖存在的抗氧化能力、抗高铬炉渣侵蚀性能与热震稳定性有待提高的问题
[0030] I. This invention addresses the challenges of high-temperature, alkaline high-chromium slag erosion, melt scouring, alternating hot and cold temperatures, and strong reducing atmosphere conditions in high-carbon ferrochrome submerged arc furnaces. By relying on the synergistic modification of three types of pre-synthesized ceramic precursors, it effectively improves the shortcomings of traditional magnesia-carbon bricks, such as easy oxidation of graphite, slag penetration and erosion, thermal shock cracking, and rapid attenuation of high-temperature strength. Within the system, multi-element alloy nitrides preferentially capture infiltrated oxygen, forming an oxidation barrier within the material and on the working surface, reducing the oxidation and burn-off rate of the graphite carbon phase and minimizing the formation of through-holes. A spinel ceramic phase is generated in situ at the two-phase interface, isolating periclase from direct solid-phase reaction with the high-chromium slag, reducing the formation of low-melting-point mineral phases. Simultaneously, the dense matrix reduces the capillary penetration capacity of the slag, alleviating erosion and spalling on the working surface. The nitride grain refinement inhibits high-temperature coarsening of periclase grains, and the crack propagation process is deflected and bridged, reducing the probability of crack penetration. A small amount of high-temperature liquid phase buffers thermal stress and fills micropores, reducing the risk of brittle cracking during hot and cold cycles. In-situ generation of nitrides and AlN ceramic particles serves as grain boundary reinforcing phases, enhancing the matrix grain boundary bonding strength at high temperatures, alleviating the problem of significant strength decay at high temperatures in conventional magnesia-carbon bricks, resisting high-speed scouring by ferrochrome alloy melts, extending the service life of the lining, and reducing the cost of furnace shutdown maintenance and refractory material consumption.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention belongs to the technical field of ceramic refractory components, specifically relating to a composite ceramic modified magnesium carbon refractory material and its preparation method. Background Technology
[0002] High-carbon ferrochrome is a key ferroalloy raw material for the production of special alloy steel and wear-resistant cast iron. The mainstream industrial method uses submerged arc furnaces for reduction smelting, accompanied by auxiliary metallurgical equipment such as electrode holders, water-cooled short meshes, tapping devices, and ladles. The hearth, slag line area, taphole, and inner wall of the ladle in the submerged arc furnace must all be lined with refractory components to isolate the high-temperature melt and maintain the stability of the furnace structure. The smelting conditions are harsh, with the furnace maintaining a high temperature of 1550–1800℃ for extended periods. Simultaneously, there is continuous chemical corrosion from alkaline high-chromium slag, scouring by ferrochrome alloy melt, and rapid heating and cooling shocks from frequent start-ups and shutdowns. Furthermore, there is a strong reducing atmosphere composed of CO and metal vapors. These conditions place stringent requirements on the comprehensive performance of the refractory lining materials, and the service life of the materials directly affects continuous production efficiency and smelting maintenance costs.
[0003] Currently, magnesia-carbon refractory bricks and magnesia-chrome bricks are commonly used as lining materials for slag lines and hearths in high-carbon ferrochrome smelting. Magnesia-carbon materials, with their excellent high-temperature resistance of periclase and the advantage of graphite not being wetted by molten slag, are suitable for alkaline metallurgical systems and are the mainstream refractory solution for high-carbon ferrochrome smelting. However, existing magnesia-carbon refractory materials still have significant shortcomings during long-term service: under high-temperature, strongly reducing atmospheres, the graphite component inside the material is easily oxidized and burned by the oxidizing medium in the furnace, forming through-pores and accelerating the penetration of high-chromium slag into the brick body; chromium trioxide in the molten slag continuously reacts with periclase in a solid-phase reaction, generating low-melting-point mineral phases, causing continuous erosion and spalling of the working surface. At the same time, traditional magnesia-carbon materials lack thermal shock stability; during peak power outages or intermittent furnace operation causing severe temperature fluctuations, the refractory lining is prone to cracking, and the expansion of these cracks leads to large-scale brick loss. Conventional magnesium-carbon products exhibit significant strength degradation at high temperatures, making them unable to withstand the high-speed mechanical erosion of molten ferrochrome and slag over extended periods. This results in frequent maintenance of critical components such as the taphole, significantly increasing production downtime losses.
[0004] Existing improvement methods mostly rely on adding single-metal antioxidants for optimization, making it difficult to simultaneously achieve oxidation resistance, slag erosion resistance, and thermal shock stability. Simply adjusting carbon content and aggregate gradation presents performance trade-offs: reducing carbon content alleviates oxidation problems but weakens the material's resistance to permeation; increasing carbon content exacerbates high-temperature oxidation damage. Therefore, it is necessary to develop novel modified magnesia-carbon refractories that comprehensively balance and enhance oxidation resistance, resistance to high-chromium slag erosion, and thermal shock stability, inhibit crack propagation, extend the service life of refractory components in submerged arc furnaces and molten iron ladles, and reduce refractory material consumption and shutdown maintenance costs during high-carbon ferrochrome smelting. Summary of the Invention
[0005] This invention addresses the shortcomings of existing traditional magnesia-carbon refractory molding components or refractory bricks, which require improvements in oxidation resistance, resistance to high-chromium slag erosion, and thermal shock stability. It provides a composite ceramic-modified magnesia-carbon refractory material and its preparation method. Designed for high-carbon chromite submerged arc furnaces operating at 1550–1800℃ under conditions of alkaline high-chromium slag erosion, melt scouring, alternating hot and cold temperatures, and strong reducing atmospheres, the material utilizes three types of pre-synthesized precursors for synergistic modification. This effectively improves the deficiencies of traditional magnesia-carbon bricks, such as easy oxidation of graphite, slag penetration and erosion, easy cracking under thermal shock, and rapid attenuation of high-temperature strength. The specific technical solution is as follows:
[0006] A composite ceramic-modified magnesia-carbon refractory material comprises the following raw materials in parts by weight: 60-70 parts of fused magnesia coarse aggregate, 15-20 parts of fused magnesia fine powder, 8-10 parts of ceramic precursor A, 6-8 parts of ceramic precursor B, 2-3 parts of precursor C, 10-12 parts of natural flake graphite, 0.2-0.6 parts of nano carbon black, 0.5-1 part of metallic aluminum powder, 3.8-5.0 parts of thermosetting phenolic resin, 0.2-0.4 parts of hexamethylenetetramine, and 1.8-3.5 parts of anhydrous ethanol.
[0007] After the refractory material is pressed into shape, it is sintered sequentially at 120-150℃ for 6-8 hours, 200-250℃ for 10-12 hours, 300-350℃ for 6-8 hours, and 800-850℃ for 3-5 hours to obtain the shaped refractory product.
[0008] Furthermore, the ceramic precursor A is prepared by dispersing alloy powder, nano-chromium trioxide, and PEG400 in anhydrous ethanol at a mass ratio of 62-65:9-12:0.3-0.5, drying, and sintering at 650-700℃; the alloy powder is a mixture of iron powder, chromium powder, silicon powder, and nickel powder at a mass ratio of 100:20-22:10-12:3-5.
[0009] Furthermore, the preparation method of the ceramic precursor A includes: mixing iron powder, chromium powder, silicon powder, and nickel powder in a mass ratio of 100:20-22:10-12:3-5 to obtain alloy powder; mixing alloy powder, nano-chromium trioxide, anhydrous ethanol, and PEG400 in a mass ratio of 62-65:9-12:150-200:0.3-0.5, dispersing evenly, and drying to obtain composite powder; sintering the composite powder at 650-700℃ for 1.5-2.5h under a high-purity nitrogen atmosphere; cooling, dispersing, and sieving to obtain ceramic precursor A.
[0010] In the above-mentioned method for preparing ceramic precursor A, the iron powder, chromium powder, silicon powder, and nickel powder are all powders that have passed through a 300-325 mesh sieve; the D50 of the nano-chromium trioxide is <200nm; the heating rate is 5-8℃ / min; and the sieving is through a 300-325 mesh sieve.
[0011] Furthermore, the ceramic precursor B is prepared by stirring chromium nitrate nonahydrate, aluminum isopropoxide, tetrabutyl titanate, and PEG600 in a mixture of anhydrous ethanol and deionized water at a mass ratio of 22-26:24-28:5-7:1.5-2.5 to obtain a sol, which is then centrifuged, spray-dried, and sintered sequentially at 350-400℃ and 480-520℃.
[0012] Furthermore, the preparation method of the ceramic precursor B includes: dissolving 22-26 parts by mass of chromium nitrate nonahydrate in a mixture of 45-50 parts by mass of anhydrous ethanol and 18-22 parts by mass of deionized water, and stirring to obtain a chromium salt solution; adding 24-28 parts by mass of aluminum isopropoxide to 55-60 parts by mass of anhydrous ethanol and stirring to obtain an aluminum isopropoxide ethanol suspension; adding the aluminum isopropoxide ethanol suspension dropwise to the chromium salt solution under a closed system at 60-65°C with stirring, and continuing to stir; adding 5-7 parts by mass of tetrabutyl titanate and continuing to stir; adding 1.5-2.5 parts by mass of PEG600 and continuing to stir to obtain a sol, centrifuging and spray drying to obtain precursor powder, sintering at 350-400°C for 3-3.5 h under a high-purity nitrogen atmosphere, then sintering at 480-520°C for 1.5-2 h, cooling, dispersing, and sieving to obtain ceramic precursor B.
[0013] In the above-mentioned method for preparing ceramic precursor B, the heating rate is 2-3℃ / min; the sieving is performed through a 300-325 mesh sieve.
[0014] Furthermore, the precursor C is prepared by mixing calcium nitrate tetrahydrate, yttrium nitrate hexahydrate, boric acid, and tetraethyl orthosilicate in an ethanol-water solution at a mass ratio of 10–12:1.5–2:1.4–1.6:15–17, adjusting the pH to 2.2–2.8, stirring to obtain a sol, gelling, drying, pulverizing, sieving, and sintering in air at 580–620°C.
[0015] Furthermore, the preparation method of the precursor C includes: dissolving 10-12 parts by mass of calcium nitrate tetrahydrate, 1.5-2 parts by mass of yttrium nitrate hexahydrate, and 1.4-1.6 parts by mass of boric acid in 90-95 parts by mass of 60-65 vol% ethanol aqueous solution, adjusting the pH to 2.2-2.8, and stirring until the solid is completely dissolved; adding 15-17 parts by mass of tetraethyl orthosilicate, stirring and hydrolyzing at 45-50°C to obtain a homogeneous sol, and allowing it to stand in a sealed container to complete gelation; drying, pulverizing, and sieving to obtain powder; sintering the powder at 580-620°C for 2-2.5 h in an air atmosphere, cooling, and ball milling to D50 ≤ 5 μm to obtain precursor C.
[0016] In the above method for preparing precursor C, the pH is adjusted with 0.5-1.0 mol / L dilute nitric acid; the sealed standing is carried out at 58-62℃ for 12-16 h to complete gelation; and the sieving is carried out through a 200-250 mesh sieve.
[0017] In the above-mentioned refractory material raw materials, the particle size distribution of the electrofused magnesia coarse aggregate is as follows: the mass ratio of 5mm ≥ particle size > 3mm, 3mm ≥ particle size > 1mm, and 1mm ≥ particle size > 0.074mm is 0.8~1.2:1.0~1.3:0.4~0.7.
[0018] In the above-mentioned refractory material raw materials, the D50 of the electrofused magnesia fine powder is 40-70 μm.
[0019] In the above-mentioned refractory material raw materials, the particle size of the natural flake graphite is ≤0.15mm.
[0020] In the above-mentioned refractory material raw materials, the nano carbon black has a D50 of 50-80 nm.
[0021] In the above-mentioned refractory material raw materials, the aluminum powder has a D50 of 1 to 5 μm.
[0022] In the above-mentioned refractory material raw materials, the thermosetting phenolic resin is a liquid thermosetting phenolic resin with a viscosity of 20-30 Pa·s at 25°C, a solid content of ≥75 wt% at 180°C, and a residual carbon content of ≥43 wt% after burning at 800°C for 7 min.
[0023] The preparation method of the above-mentioned composite ceramic modified magnesium carbon refractory material includes the following steps:
[0024] S1: Premix fused magnesia fine powder, nano carbon black and metallic aluminum powder evenly to obtain premixed fine powder;
[0025] S2: The fused magnesia coarse aggregate is premixed evenly, natural flake graphite is added and mixed evenly, then anhydrous ethanol is added and mixed evenly, ceramic precursor A, ceramic precursor B, precursor C and premixed fine powder are added in sequence and mixed evenly, and finally thermosetting phenolic resin and hexamethylenetetramine are added and mixed evenly to obtain mud and bridging material.
[0026] S3: The clay is poured into the mold and pressed into shape. The density of the formed blank is controlled between 2.98 and 3.08 g / cm³. 3 ;
[0027] S4: Under the protection of high-purity nitrogen, the formed green body is sintered at 120-150℃ for 6-8 hours at a rate of 1-2℃ / min; then sintered at 200-250℃ for 10-12 hours at a rate of 1-2℃ / min; then sintered at 300-350℃ for 6-8 hours at a rate of 2-3℃ / min; then sintered at 800-850℃ for 3-5 hours at a rate of 2-3℃ / min; then cooled and removed from the furnace to obtain the formed refractory product.
[0028] In step S2 of the above-mentioned method for preparing refractory materials, the mixing control temperature is below 45°C; the accumulator is clay placed in a closed environment at 23-28°C and 40-60% relative humidity for 20-24 hours; in step S3, the pressing pressure is 85-135 MPa; in step S4, the cooling rate is: below 2°C / min to 350-400°C, and below 3°C / min to 30-60°C.
[0029] The present invention provides a composite ceramic-modified magnesia-carbon refractory material and its preparation method, which have the following beneficial effects:
[0030] I. This invention addresses the challenges of high-temperature, alkaline high-chromium slag erosion, melt scouring, alternating hot and cold temperatures, and strong reducing atmosphere conditions in high-carbon ferrochrome submerged arc furnaces. By relying on the synergistic modification of three types of pre-synthesized ceramic precursors, it effectively improves the shortcomings of traditional magnesia-carbon bricks, such as easy oxidation of graphite, slag penetration and erosion, thermal shock cracking, and rapid attenuation of high-temperature strength. Within the system, multi-element alloy nitrides preferentially capture infiltrated oxygen, forming an oxidation barrier within the material and on the working surface, reducing the oxidation and burn-off rate of the graphite carbon phase and minimizing the formation of through-holes. A spinel ceramic phase is generated in situ at the two-phase interface, isolating periclase from direct solid-phase reaction with the high-chromium slag, reducing the formation of low-melting-point mineral phases. Simultaneously, the dense matrix reduces the capillary penetration capacity of the slag, alleviating erosion and spalling on the working surface. The nitride grain refinement inhibits high-temperature coarsening of periclase grains, and the crack propagation process is deflected and bridged, reducing the probability of crack penetration. A small amount of high-temperature liquid phase buffers thermal stress and fills micropores, reducing the risk of brittle cracking during hot and cold cycles. In-situ generation of nitrides and AlN ceramic particles serves as grain boundary reinforcing phases, enhancing the matrix grain boundary bonding strength at high temperatures, alleviating the problem of significant strength decay at high temperatures in conventional magnesia-carbon bricks, resisting high-speed scouring by ferrochrome alloy melts, extending the service life of the lining, and reducing the cost of furnace shutdown maintenance and refractory material consumption.
[0031] II. Ceramic precursor A employs a multi-component metal alloy powder and nano-chromium trioxide liquid-phase dispersion, followed by nitrogen-enhanced staged pre-firing. This process allows the Fe-Cr-Si-Ni alloy and nano-chromium oxide to fully react, generating stable nitride and carbonitride composite powders. Nitrogen-protected pre-firing prevents premature oxidation of the metal powder, ensuring the finished bricks retain oxygen-absorbing activity during firing. Nano-chromium trioxide simultaneously participates in the nitriding reaction, increasing the proportion of chromium-based dense phase in the oxygen-barrier oxide film. The multi-metal alloy components broaden the oxidation reaction temperature range, providing sustained antioxidant effects from low to high temperatures.
[0032] III. Ceramic precursor B achieves uniform molecular-level mixing of multi-metal ions using the sol-gel method, resulting in a uniform and continuous aluminum-chromium-titanium composite spinel phase after firing. The low-temperature stage removes all organic matter and nitrate decomposition gases, preventing concentrated gas generation and the formation of interconnected pores during brick firing. Segmented sintering gradually completes the crystallization of the crystalline phase, improving the chemical stability of the spinel and enhancing the interfacial slag-resistant isolation effect. A small amount of high thermal conductivity AlN particles are generated in situ from the titanium-aluminum component, improving the material's thermal conductivity and reducing the temperature difference across the thermal shock cross-section.
[0033] IV. In the preparation of precursor C, calcium-yttrium-boron-silicon polyol salt is used to hydrolyze the sol. Dilute nitric acid is used to regulate the pH range to ensure uniform hydrolysis. Low-temperature closed-loop gelation is performed, followed by air pre-calcination at 580–620°C to remove nitrates and organic solvents. During the calcination of the finished product, there is no significant gas generation or pore formation. The multi-component silicate composite powder generates a liquid phase in the medium-low temperature range, reducing the sintering activation energy. Rare earth yttrium doping optimizes the high-temperature viscoelasticity of the liquid phase, which can both fill pores and buffer thermal stress without significantly reducing the high-temperature structural strength.
[0034] V. Four-stage stepped nitrogen sintering process: Low-temperature segmented slow heating and holding can slowly remove ethanol, moisture, and small molecule volatiles of resin, ensuring stable precipitation of volatiles without generating internal high-pressure pores or delamination cracks; the resin gradually solidifies and pre-carbonizes, forming a preliminary continuous carbon skeleton. The 800-850℃ high-temperature range provides the temperature range for phase transformation, nitriding, and spinel crystallization reactions of the three types of ceramic precursors. Gradient cooling regime: slow cooling above 350℃, with moderate acceleration in the low-temperature range, controls the temperature difference between the surface and the interior of the green body, eliminates residual thermal stress from cooling, and prevents spontaneous cracking of finished bricks after leaving the kiln. Detailed Implementation
[0035] The following provides some embodiments for further illustration, but the present invention is not limited to these embodiments.
[0036] Example 1
[0037] A composite ceramic-modified magnesia-carbon refractory material comprises the following raw materials in parts by weight: 65 parts of fused magnesia coarse aggregate, 18 parts of fused magnesia fine powder, 9 parts of ceramic precursor A, 7 parts of ceramic precursor B, 2.5 parts of precursor C, 11 parts of natural flake graphite, 0.4 parts of nano carbon black, 0.7 parts of metallic aluminum powder, 4.4 parts of thermosetting phenolic resin, 0.3 parts of hexamethylenetetramine, and 2.3 parts of anhydrous ethanol.
[0038] The specifications for fused magnesia coarse aggregate are as follows: MgO content 98.0 wt%; particle size distribution: mass ratio of 5mm ≥ particle size > 3mm, 3mm ≥ particle size > 1mm, 1mm ≥ particle size > 0.074mm 1:1.2:0.55. Specifications for fused magnesia fine powder: D50 = 58μm, MgO content 98.0 wt%. Specifications for natural flake graphite: fixed carbon content 95 wt%, particle size range ≤ 0.15mm. Specifications for nano-carbon black: D50 = 60nm. Specifications for metallic aluminum powder: D50 = 3μm, metallic aluminum purity 99.0 wt%. Thermosetting phenolic resin is a liquid thermosetting phenolic resin with a viscosity of 26 Pa·s at 25℃, a solid content of 76 wt% at 180℃, and a residual carbon content of 45 wt% after calcination at 800℃ for 7 minutes. Specifications for hexamethylenetetramine: purity 98 wt%, passing through a 200-mesh sieve.
[0039] The preparation method of ceramic precursor A includes: iron powder, chromium powder, silicon powder, and nickel powder are all powders that have passed through a 300-mesh sieve; iron powder, chromium powder, silicon powder, and nickel powder are mixed in an airflow at a mass ratio of 100:21:11:4 and passed through a 300-mesh sieve to obtain alloy powder; alloy powder, nano-chromium trioxide (D50=160nm), anhydrous ethanol, and PEG400 are mixed in a mass ratio of 64:11:180:0.4, ultrasonically stirred and dispersed at 25℃ and 350r / min for 35min, and after uniform dispersion, vacuum dried at 80℃ for 10h to obtain composite powder; composite powder is placed in a tube furnace, and high-purity nitrogen is introduced at room temperature to purge the furnace air for 12min to replace the furnace air, and sintered at 6℃ / min to 680℃ for 2h under the protection of high-purity nitrogen atmosphere at a flow rate of 0.8L / min; the furnace is cooled to below 60℃ under nitrogen protection, taken out, dispersed, and passed through a 300-mesh sieve to obtain ceramic precursor A.
[0040] The preparation method of ceramic precursor B includes: dissolving 24 parts by mass of chromium nitrate nonahydrate in a mixture of 48 parts by mass of anhydrous ethanol and 20 parts by mass of deionized water, stirring at 320 r / min for 70 min to obtain a chromium salt solution; adding 26 parts by mass of aluminum isopropoxide to 58 parts by mass of anhydrous ethanol and stirring until dispersed to obtain an aluminum isopropoxide ethanol suspension; under sealed conditions at 62℃ and stirring at 320 r / min, uniformly adding the aluminum isopropoxide ethanol suspension to the chromium salt solution over 35 min, stirring for 100 min after the addition is complete; uniformly adding 6 parts by mass of tetrabutyl titanate over 60 min, and continuing stirring for another 60 min after the addition is complete. In; add 2 parts of PEG600 and stir for 100 min to obtain a sol; centrifuge and spray dry: inlet air 190℃, outlet air 105℃, centrifuge speed 13000 rpm to obtain precursor powder; place the precursor powder in a tube furnace, purge the furnace air with high-purity nitrogen at room temperature for 12 min to replace the furnace air, and sinter at 380℃ for 3 h at a flow rate of 0.8 L / min under high-purity nitrogen atmosphere protection, then sinter at 500℃ for 2 h at a flow rate of 2.5℃ / min; cool with the furnace under nitrogen protection to below 60℃, take out, break up and pass through a 300 mesh sieve to obtain ceramic precursor B.
[0041] The preparation method of precursor C includes: dissolving 11 parts by mass of calcium nitrate tetrahydrate, 1.8 parts by mass of yttrium nitrate hexahydrate, and 1.5 parts by mass of boric acid in 92 parts by mass of 62 vol% ethanol aqueous solution; adjusting the pH to 2.5 with 0.8 mol / L dilute nitric acid; stirring at 24℃ and 280 r / min for 55 min until the solid is completely dissolved and there are no fine suspended particles; uniformly adding 16 parts by mass of tetraethyl orthosilicate over 35 min; stirring and hydrolyzing at 48℃ and 280 r / min for 3 h to obtain a homogeneous sol; allowing it to stand in a sealed container at 60℃ for 14 h to complete gelation; drying in a forced-air environment at 115℃ for 18 h; pulverizing and passing through a 200-mesh sieve to obtain powder; sintering the powder at 600℃ for 2 h in an air atmosphere; ball milling to D50 = 3 μm after natural cooling to obtain precursor C.
[0042] The preparation method of the above-mentioned composite ceramic modified magnesium carbon refractory material includes the following steps:
[0043] S1: Weigh all raw materials according to the mass fractions; premix the fused magnesia fine powder, nano carbon black, and metallic aluminum powder evenly to obtain premixed fine powder for later use;
[0044] S2: In a counter-current mixer at a stirring speed of 30 r / min, first, fused magnesia coarse aggregate is added and premixed for 3 min, then natural flake graphite is added and mixed for 5 min; then anhydrous ethanol is added and mixed for 5 min; ceramic precursor A, ceramic precursor B, precursor C and premixed fine powder are added in sequence and mixed for 9 min; finally, thermosetting phenolic resin and hexamethylenetetramine are added and mixed for 18 min to obtain mud; the equipment is kept relatively sealed throughout the process to reduce the volatilization of anhydrous ethanol; water cooling and temperature control are used throughout the process to keep the mud temperature <45℃; the mud is placed in a sealed environment with a temperature range of 23~28℃ and a relative humidity range of 40~60% for 22 h.
[0045] S3: The clay is injected into the mold, and a process of multiple light pressure venting and one final pressure molding is adopted. The molding pressure is 85-135MPa, and the density of the molded blank is controlled between 2.98-3.08g / cm³. 3 ;
[0046] S4: The formed green body is sintered at 130℃ for 7 hours under continuous high-purity nitrogen protection at a rate of 1.5℃ / min; then sintered at 220℃ for 11 hours at a rate of 1.5℃ / min; then sintered at 320℃ for 7 hours at a rate of 2.5℃ / min; then sintered at 820℃ for 4 hours at a rate of 2.5℃ / min; then cooled to 380℃ at a rate of less than 2℃ / min, and then cooled to 50℃ at a rate of less than 3℃ / min, and then removed from the furnace to obtain the formed refractory product.
[0047] Example 2
[0048] A composite ceramic modified magnesia-carbon refractory material comprises the following raw materials in parts by weight: 60 parts of fused magnesia coarse aggregate, 20 parts of fused magnesia fine powder, 8 parts of ceramic precursor A, 8 parts of ceramic precursor B, 2 parts of precursor C, 12 parts of natural flake graphite, 0.2 parts of nano carbon black, 1 part of metallic aluminum powder, 3.8 parts of thermosetting phenolic resin, 0.4 parts of hexamethylenetetramine, and 1.8 parts of anhydrous ethanol.
[0049] The specifications for fused magnesia coarse aggregate are as follows: MgO content 98.3wt%; particle size distribution: mass ratio of 5mm ≥ particle size > 3mm, 3mm ≥ particle size > 1mm, 1mm ≥ particle size > 0.074mm 0.8:1.0:0.4. Specifications for fused magnesia fine powder: D50 = 40μm, MgO content 98.2wt%. Specifications for natural flake graphite: fixed carbon content 95.5wt%, particle size range ≤ 0.15mm. Specifications for nano-carbon black: D50 = 50nm. Specifications for metallic aluminum powder: D50 = 1μm, metallic aluminum purity 99.4wt%. Thermosetting phenolic resin is a liquid thermosetting phenolic resin with a viscosity of 20Pa·s at 25℃, a solid content of 75.5wt% at 180℃, and a residual carbon content of 43.7wt% after calcination at 800℃ for 7 minutes. Specifications for hexamethylenetetramine: purity 99wt%, passing through a 200-mesh sieve.
[0050] The preparation method of ceramic precursor A includes: iron powder, chromium powder, silicon powder, and nickel powder are all powders that have passed through a 300-mesh sieve; iron powder, chromium powder, silicon powder, and nickel powder are mixed in an airflow at a mass ratio of 100:22:10:5 and passed through a 300-mesh sieve to obtain alloy powder; alloy powder, nano-chromium trioxide (D50=130nm), anhydrous ethanol, and PEG400 are mixed in a mass ratio of 62:12:150:0.5, ultrasonically stirred and dispersed at 20℃ and 400r / min for 30min, and after uniform dispersion, vacuum dried at 85℃ for 8h to obtain composite powder; composite powder is placed in a tube furnace, and high-purity nitrogen is introduced at room temperature to purge the furnace air for 15min, and sintered at 650℃ for 2.5h under the protection of high-purity nitrogen atmosphere at a flow rate of 0.5L / min, with the temperature increased at 8℃ / min; nitrogen protection is used to cool the furnace to below 60℃, and the powder is taken out, dispersed, and passed through a 300-mesh sieve to obtain ceramic precursor A.
[0051] The preparation method of ceramic precursor B includes: dissolving 22 parts by mass of chromium nitrate nonahydrate in a mixture of 45 parts by mass of anhydrous ethanol and 18 parts by mass of deionized water, stirring at 300 r / min for 80 min to obtain a chromium salt solution; adding 24 parts by mass of aluminum isopropoxide to 60 parts by mass of anhydrous ethanol and stirring until dispersed to obtain an aluminum isopropoxide ethanol suspension; under sealed conditions at 60℃ and stirring at 350 r / min, uniformly adding the aluminum isopropoxide ethanol suspension to the chromium salt solution over 25 min, stirring for 120 min after the addition is complete; uniformly adding 7 parts by mass of tetrabutyl titanate over 50 min, and continuing stirring for another 50 min after the addition is complete. Add 2.5 parts of PEG600 and stir for 90 min to obtain a sol; centrifuge and spray dry: inlet air 200℃, outlet air 100℃, centrifuge speed 14000 rpm to obtain precursor powder; place the precursor powder in a tube furnace, purge the furnace air with high-purity nitrogen at room temperature for 10 min to replace the furnace air, and sinter at 400℃ for 3 h at a flow rate of 1.0 L / min under high-purity nitrogen atmosphere protection, then sinter at 480℃ for 2 h at a flow rate of 2℃ / min, and then sinter at 480℃ for 2 h at a flow rate of 3℃ / min; cool with nitrogen protection to below 60℃, take out, break up and pass through a 300 mesh sieve to obtain ceramic precursor B.
[0052] The preparation method of precursor C includes: dissolving 10 parts by mass of calcium nitrate tetrahydrate, 2 parts by mass of yttrium nitrate hexahydrate, and 1.4 parts by mass of boric acid in 95 parts by mass of 60 vol% ethanol aqueous solution; adjusting the pH to 2.2 with 1.0 mol / L dilute nitric acid, stirring at 28℃ and 250 r / min for 60 min until the solid is completely dissolved and there are no fine suspended particles; uniformly adding 17 parts by mass of tetraethyl orthosilicate over 30 min, stirring at 45℃ and 300 r / min for 2.5 h to obtain a homogeneous sol, and allowing it to stand in a sealed container at 62℃ for 12 h to complete gelation; drying in a forced-air environment at 120℃ for 16 h, pulverizing through a 250 mesh sieve to obtain powder; sintering the powder at 580℃ for 2.5 h in an air atmosphere, and ball milling to D50 = 2 μm after natural cooling to obtain precursor C.
[0053] The preparation method of the above-mentioned composite ceramic modified magnesium carbon refractory material includes the following steps:
[0054] S1: Weigh all raw materials according to the mass fractions; premix the fused magnesia fine powder, nano carbon black, and metallic aluminum powder evenly to obtain premixed fine powder for later use;
[0055] S2: In a counter-current mixer at a stirring speed of 20 r / min, first, fused magnesia coarse aggregate is added and premixed for 4 min, then natural flake graphite is added and mixed for 8 min; next, anhydrous ethanol is added and mixed for 4 min; ceramic precursor A, ceramic precursor B, precursor C and premixed fine powder are added in sequence and mixed for 8 min; finally, thermosetting phenolic resin and hexamethylenetetramine are added and mixed for 20 min to obtain mud; the equipment is kept relatively sealed throughout the process to reduce the volatilization of anhydrous ethanol; water cooling and temperature control are used throughout the process to keep the mud temperature <45℃; the mud is placed in a sealed environment with a temperature range of 23~28℃ and a relative humidity range of 40~60% for 20 h.
[0056] S3: The clay is injected into the mold, and a process of multiple light pressure venting and one final pressure molding is adopted. The molding pressure is 85-135MPa, and the density of the molded blank is controlled between 2.98-3.08g / cm³. 3 ;
[0057] S4: The formed green body is sintered at 150℃ for 6 hours under continuous high-purity nitrogen protection at a rate of 1℃ / min; then sintered at 200℃ for 12 hours at a rate of 2℃ / min; then sintered at 350℃ for 6 hours at a rate of 2℃ / min; then sintered at 800℃ for 5 hours at a rate of 3℃ / min; then cooled to 350℃ at a rate of less than 2℃ / min, and then cooled to 60℃ at a rate of less than 3℃ / min, and then removed from the furnace to obtain the formed refractory product.
[0058] Example 3
[0059] A composite ceramic modified magnesia-carbon refractory material comprises the following raw materials in parts by weight: 70 parts of fused magnesia coarse aggregate, 15 parts of fused magnesia fine powder, 10 parts of ceramic precursor A, 6 parts of ceramic precursor B, 3 parts of precursor C, 10 parts of natural flake graphite, 0.6 parts of nano carbon black, 0.5 parts of metallic aluminum powder, 5 parts of thermosetting phenolic resin, 0.2 parts of hexamethylenetetramine, and 3.5 parts of anhydrous ethanol.
[0060] The specifications for fused magnesia coarse aggregate are as follows: MgO content 98.7wt%; particle size distribution: mass ratio of 5mm ≥ particle size > 3mm, 3mm ≥ particle size > 1mm, 1mm ≥ particle size > 0.074mm 1.2:1.3:0.7. Specifications for fused magnesia fine powder: D50 = 70μm, MgO content 98.5wt%. Specifications for natural flake graphite: fixed carbon content 97wt%, particle size range ≤0.15mm. Specifications for nano-carbon black: D50 = 80nm. Specifications for metallic aluminum powder: D50 = 5μm, metallic aluminum purity 99.1wt%. Thermosetting phenolic resin is a liquid thermosetting phenolic resin with a viscosity of 30Pa·s at 25℃, a solid content of 76.3wt% at 180℃, and a residual carbon content of 45wt% after calcination at 800℃ for 7 minutes. Specifications for hexamethylenetetramine: purity 98.4wt%, passing through a 250-mesh sieve.
[0061] The preparation method of ceramic precursor A includes: iron powder, chromium powder, silicon powder, and nickel powder are all powders that have passed through a 325-mesh sieve; iron powder, chromium powder, silicon powder, and nickel powder are mixed in an airflow at a mass ratio of 100:20:12:3 and passed through a 325-mesh sieve to obtain alloy powder; alloy powder, nano-chromium trioxide (D50=120nm), anhydrous ethanol, and PEG400 are mixed in a mass ratio of 65:9:200:0.3, ultrasonically stirred and dispersed at 30℃ and 300r / min for 40min, and after uniform dispersion, vacuum dried at 75℃ for 12h to obtain composite powder; composite powder is placed in a tube furnace, and high-purity nitrogen is introduced at room temperature to purge the furnace air for 10min, and sintered at 700℃ for 1.5h at a flow rate of 1.0L / min under high-purity nitrogen atmosphere protection, with the temperature increased to 5℃ / min; nitrogen protection is used to cool the furnace to below 60℃, and the powder is taken out, dispersed, and passed through a 325-mesh sieve to obtain ceramic precursor A.
[0062] The preparation method of ceramic precursor B includes: dissolving 26 parts by mass of chromium nitrate nonahydrate in a mixture of 50 parts by mass of anhydrous ethanol and 22 parts by mass of deionized water, stirring at 350 r / min for 60 min to obtain a chromium salt solution; adding 28 parts by mass of aluminum isopropoxide to 55 parts by mass of anhydrous ethanol and stirring until dispersed to obtain an aluminum isopropoxide ethanol suspension; under sealed conditions at 65℃ and stirring at 300 r / min, uniformly adding the aluminum isopropoxide ethanol suspension to the chromium salt solution over 40 min, stirring for 90 min after the addition is complete; uniformly adding 5 parts by mass of tetrabutyl titanate over 70 min, and continuing stirring for another 70 min after the addition is complete. Add 1.5 parts of PEG600 and stir for 110 min to obtain a sol; centrifuge and spray dry: inlet air 180℃, outlet air 110℃, centrifuge speed 12000 rpm to obtain precursor powder; place the precursor powder in a tube furnace, purge the furnace air with high-purity nitrogen at room temperature for 15 min to replace the furnace air, and sinter at 3℃ / min to 350℃ for 3.5 h under the protection of high-purity nitrogen atmosphere at a flow rate of 0.5 L / min, and then sinter at 2℃ / min to 520℃ for 1.5 h; cool with nitrogen protection to below 60℃, take out, break up and pass through a 325 mesh sieve to obtain ceramic precursor B.
[0063] The preparation method of precursor C includes: dissolving 12 parts by mass of calcium nitrate tetrahydrate, 1.5 parts by mass of yttrium nitrate hexahydrate, and 1.6 parts by mass of boric acid in 90 parts by mass of 65 vol% ethanol aqueous solution; adjusting the pH to 2.8 with 0.5 mol / L dilute nitric acid, stirring at 20℃ and 300 r / min for 50 min until the solid is completely dissolved and there are no fine suspended particles; uniformly adding 15 parts by mass of tetraethyl orthosilicate over 40 min, stirring at 50℃ and 250 r / min for 3.5 h to obtain a homogeneous sol, and allowing it to stand in a sealed container at 58℃ for 16 h to complete gelation; drying in a forced-air environment at 110℃ for 20 h, pulverizing and passing through a 200-mesh sieve to obtain powder; sintering the powder at 620℃ for 2 h in an air atmosphere, and ball milling to D50 = 5 μm after natural cooling to obtain precursor C.
[0064] The preparation method of the above-mentioned composite ceramic modified magnesium carbon refractory material includes the following steps:
[0065] S1: Weigh all raw materials according to the mass fractions; premix the fused magnesia fine powder, nano carbon black, and metallic aluminum powder evenly to obtain premixed fine powder for later use;
[0066] S2: In a counter-current mixer at a stirring speed of 35 r / min, first, fused magnesia coarse aggregate is added and premixed for 2 min, then natural flake graphite is added and mixed for 6 min; then anhydrous ethanol is added and mixed for 4 min; ceramic precursor A, ceramic precursor B, precursor C and premixed fine powder are added in sequence and mixed for 10 min; finally, thermosetting phenolic resin and hexamethylenetetramine are added and mixed for 15 min to obtain mud; the equipment is kept relatively sealed throughout the process to reduce the volatilization of anhydrous ethanol; water cooling and temperature control are used throughout the process to keep the mud temperature <45℃; the mud is placed in a sealed environment with a temperature range of 23-28℃ and a relative humidity range of 40-60% for 24 h.
[0067] S3: The clay is injected into the mold, and a process of multiple light pressure venting and one final pressure molding is adopted. The molding pressure is 85-135MPa, and the density of the molded blank is controlled between 2.98-3.08g / cm³. 3 ;
[0068] S4: The formed green body is sintered at 120°C for 8 hours under continuous high-purity nitrogen protection at a rate of 2°C / min; then sintered at 250°C for 10 hours at a rate of 1°C / min; then sintered at 300°C for 8 hours at a rate of 3°C / min; then sintered at 850°C for 3 hours at a rate of 2°C / min; then cooled to 400°C at a rate of less than 2°C / min, and then cooled to 30°C at a rate of less than 3°C / min, and then removed from the furnace to obtain the formed refractory product.
[0069] The raw material specifications involved in the above embodiments are as follows: The thermosetting phenolic resin is sourced from Henan Bangnai New Materials Co., Ltd., and is a liquid thermosetting phenolic resin. PFNH-125 specifications: viscosity 20-30 Pa·s at 25℃, solid content above 75wt% at 180℃, and residual carbon content above 43wt% at 800℃ for 7 minutes. PEG400 is polyethylene glycol with a molecular weight of approximately 400, sourced from Jingzhou Yinjie Chemical Co., Ltd., with an average molecular weight of 380-420 and a purity above 99%. PEG600 is polyethylene glycol with a molecular weight of approximately 400, sourced from Jingzhou Yinjie Chemical Co., Ltd., with an average molecular weight of 570-630 and a purity above 99%. The purity of iron powder, chromium powder, silicon powder, nickel powder, nano-chromium trioxide, chromium nitrate nonahydrate, aluminum isopropoxide, and boric acid is all above 99%. The purity of tetrabutyl titanate, calcium nitrate tetrahydrate, yttrium nitrate hexahydrate, and tetraethyl orthosilicate is all above 98%.
[0070] Comparative Example 1
[0071] The difference from Example 1 is that ceramic precursor A is changed to 3 parts and ceramic precursor B is changed to 13 parts.
[0072] Comparative Example 2
[0073] The difference from Example 1 is that ceramic precursor A is changed to 13 parts and ceramic precursor B is changed to 3 parts.
[0074] Comparative Example 3
[0075] The difference from Example 1 is that ceramic precursor A is not added.
[0076] Comparative Example 4
[0077] The difference from Example 1 is that ceramic precursor B is not added.
[0078] Comparative Example 5
[0079] The difference from Example 1 is that ceramic precursor A and ceramic precursor B are not added at the same time.
[0080] Comparative Example 6
[0081] The difference from Example 1 is that the precursor C is not added.
[0082] Comparative Example 7
[0083] The difference from Example 1 is that the precursor C is changed to 10 parts.
[0084] Comparative Example 8
[0085] The difference from Example 1 is that the ceramic precursor A is directly replaced by composite powder without sintering.
[0086] Comparative Example 9
[0087] The difference from Example 1 is that the ceramic precursor B is directly replaced by precursor powder without sintering.
[0088] Comparative Example 10
[0089] The difference from Example 1 is that the precursor C is directly replaced by powder that has been dried by forced air and then pulverized, without sintering.
[0090] Comparative Example 11
[0091] The difference from Example 1 is that the S4 sintering process is changed to: sintering at 130°C at 1.5°C / min for 7 hours; sintering at 220°C at 1.5°C / min for 11 hours; sintering at 320°C at 2.5°C / min for 7 hours; and sintering at 500°C at 2.5°C / min for 4 hours.
[0092] I. Bulk density and apparent porosity:
[0093] Sample specifications: 50mm×50mm×50mm cube.
[0094] Test Procedure: The specimen was dried in a 110℃ oven for 24 hours until constant weight. After cooling to room temperature, the dried mass (m1) was measured. The specimen was then vacuum-saturated with water for 30 minutes, followed by immersion in atmospheric pressure for 30 minutes. The saturated specimen was then suspended in water, completely submerged without contact with the container wall, and the suspended mass (m2) was measured. Finally, the specimen was removed, the surface water was gently wiped off, and the saturated wet mass (m3) was measured. Bulk density ρ (g / cm³) 3 ) = m1 × ρwater / (m3 - m2); Apparent porosity P (%) = [(m3 - m1) / (m3 - m2)] × 100%.
[0095] II. Compressive strength at room temperature:
[0096] Sample specifications: 50mm×50mm×50mm cube.
[0097] Testing Procedure: The specimen was dried in a 110℃ oven for 24 hours and then cooled to room temperature. A universal testing machine was used to uniformly load the specimen at a loading rate of 0.5 MPa / s until failure, and the maximum failure load F was recorded. The compressive strength σ (MPa) = F / S, where S is the area of the specimen subjected to pressure (mm²). 2 ).
[0098] III. Flexural strength at room temperature:
[0099] Sample specifications: 160mm×40mm×40mm cuboid.
[0100] Testing Procedure: The specimen was dried in a 110℃ oven for 24 hours and then cooled to room temperature. A three-point bending test was performed with a support span of 125mm, applying a uniform load at a rate of 0.15MPa / s until fracture. The maximum load F at fracture was recorded. Flexural strength σ (MPa) = 3FL / (2bh) 2 F is the fracture load (N), L is the span (mm), b is the specimen width (mm), and h is the specimen height (mm).
[0101] IV. Flexural strength at 1400℃:
[0102] Sample specifications: 150mm×25mm×25mm cuboid.
[0103] Testing Procedure: Under a nitrogen atmosphere, the temperature is increased to 1400℃ at a rate of 5℃ / min and held for 30 minutes. Using the three-point bending method, with a support span of 125mm, a uniform loading rate of 0.15MPa / s is applied until fracture. The maximum load F at fracture is recorded. Flexural strength σ (MPa) = 3FL / (2bh) 2 F is the fracture load (N), L is the span (mm), and b and h are the specimen width and height (mm), respectively.
[0104] V. High-temperature oxidation resistance at 1300℃:
[0105] Sample specifications: 50mm×50mm×50mm cube.
[0106] Testing Procedure: After drying the specimen at 110℃ to constant weight, weigh the initial mass m0; heat to 1300℃ in air at 5℃ / min and hold for 3 hours; cool to room temperature in the furnace, gently brush off the loose oxide scale on the surface with a soft brush, do not grind or cut the substrate, and weigh the residual mass m1; oxidation weight loss rate η (%) = [(m0-m1) / m0] × 100%. Cut along the center line of the specimen and measure the delamination thickness in four symmetrical directions (top, bottom, left, and right), and take the arithmetic mean.
[0107] VI. Thermal shock resistance at 1100℃:
[0108] Sample specifications: 230mm×114mm×65mm straight brick.
[0109] Test Procedure: Before the test, the sample was dried in a 110℃ oven to constant weight. The sample was then placed in an electric furnace preheated to 1100℃ and kept at that temperature for 20 minutes. After removal, the sample was vertically immersed in flowing water at 25℃ along its length to a depth of 50mm ± 5mm, with a minimum distance of 20mm from the bottom of the water tank. It was then rapidly cooled for 3 minutes to complete one thermal cycle. The sample was then removed and left in the air for at least 5 minutes before being dried at 110℃ to constant weight. The thermal shock cycle was repeated, and the thermal shock failure was determined based on the area of sample peeling and breakage accounting for 50% to 55% of the total area of the test end face. The number of cycles was recorded.
[0110] VII. Permanent linear change rate at 1600℃:
[0111] Sample specifications: 50mm×50mm×50mm cube.
[0112] Testing Procedure: Mark fixed measurement points at room temperature, measure the side lengths of the sample along three mutually perpendicular axes, and take the arithmetic mean initial length L0; under nitrogen protection, heat to 1600℃ at 5℃ / min, hold for 3 hours, and cool to room temperature with the furnace; repeat the measurement of the three side lengths at the same marked points, and take the arithmetic mean length L1. Permanent linear change rate ΔL (%) = [(L1-L0) / L0] × 100%.
[0113] 8. Slag erosion resistance in the 1600℃ static crucible method:
[0114] Sample specifications: 100mm×100mm×100mm cube, with a cylindrical crucible hole of 40mm diameter and 50mm depth in the center.
[0115] The experimental slag mix (mass fraction) was: 38% Cr2O3, 26% MgO, 22% CaO, and 14% SiO2.
[0116] Testing steps: Fill the crucible hole with mixed slag powder and gently vibrate to compact it; heat to 1600℃ at 5℃ / min under nitrogen protection atmosphere and hold for 4h; after cooling, cut the sample along the central axis and determine the maximum erosion depth.
[0117] For each of the above test items, there are 5 parallel samples. After removing abnormal data (deviations exceeding ±10% of the average value), at least 3 samples are used to calculate the average value. The test results are shown in Table 1 below.
[0118] Table 1 Performance Test Results
[0119]
[0120] The materials in the above three sets of embodiments have their performance optimized from multiple dimensions, including anti-oxidation barrier, slag erosion interface protection, and sintering densification. Ceramic precursor A, derived from Fe-Cr nitrides, refines periclase grains through grain boundary pinning. Simultaneously, the metal alloy components preferentially react with infiltrated oxygen to generate an oxidation barrier, reducing the oxidation rate of the internal carbon phase. Ceramic precursor B, prepared as a sol-gel, forms a ceramic layer at the magnesia-graphite two-phase interface after sintering, reducing the direct contact area between the slag and periclase. The Ti-Al component fills the active defect sites on the graphite surface, simultaneously improving anti-oxidation performance. A small amount of AlN particles are generated in situ to optimize the material's thermal conductivity and alleviate thermal stress concentration. Precursor C, sintered, generates a low-temperature silicate liquid phase, promoting particle rearrangement, increasing the density of the green body, and reducing the proportion of open pores. A small amount of liquid phase fills the micropores generated during molding and thermal cycling. These three types of precursors complement each other, forming a composite modification system that provides oxygen diffusion barrier, slag interface protection, and thermal stress buffering, simultaneously improving the material's anti-oxidation, anti-slag erosion, thermal shock stability, and high-temperature mechanical properties.
[0121] Precursor C is formulated from calcium nitrate tetrahydrate, yttrium nitrate hexahydrate, boric acid, and tetraethyl orthosilicate. After pre-calcination in air at 580–620°C, it undergoes decomposition and solid-phase reaction to generate a CaO-Y₂O₃-B₂O₃-SiO₂ composite oxide powder. This composite oxide powder is the only phase in this system capable of forming a sintering-aiding liquid phase. B₂O₃, obtained from the decomposition of boric acid, is the core fluxing component, significantly reducing the eutectic temperature of the system, allowing the material to generate a flowable liquid phase at around 800°C. CaO is used to adjust the viscosity of the liquid phase and improve its wetting effect on magnesia particles. The rare earth component Y₂O₃ refines the thin liquid phase layer at grain boundaries, inhibiting excessive softening and creep of the liquid phase at high temperatures and preventing a significant decrease in the material's high-temperature strength. SiO₂ constructs a silicate glass network framework, ensuring the liquid phase maintains a certain structural stability under high-temperature conditions.
[0122] With the decrease in the amount of ceramic precursor A added in Comparative Example 1, the total amount of nitride-reinforced phase generated decreased, the grain boundary pinning and grain refinement effect weakened, and the continuity of the oxygen-barrier oxide film formed by Fe-Cr nitride decreased. Excess ceramic precursor B aggregated in the matrix, the difference in thermal expansion coefficients between the spinel phase and the periclase matrix increased, the internal residual stress of the material increased, micropores were easily generated, oxygen and slag infiltration channels increased, and mechanical strength, oxidation resistance, slag resistance and thermal shock resistance all showed a slight decrease.
[0123] In Comparative Example 2, excessive addition of ceramic precursor A leads to the agglomeration of nitride particles, forming stress concentration points that are prone to crack initiation sites under thermal alternation conditions. Insufficient content of ceramic precursor B reduces the amount of spinel protective layer formed at the interface, making it easier for high-chromium slag to react directly with periclase to form low-melting-point mineral phases, thus accelerating the erosion of the working surface. Excessive nitride oxidation increases oxide porosity, thereby increasing oxidation weight loss and delamination thickness.
[0124] After removing ceramic precursor A in Comparative Example 3, the system lacked Fe-Cr nitride anti-oxidation and grain-refining phases, and only relied on a small amount of metallic aluminum powder to achieve limited anti-oxidation protection. After the aluminum powder was consumed, there was no continuous oxygen-barrier component, and the thickness of the graphite oxidation decarburization layer increased significantly. The periclase grains coarsened significantly at high temperatures, the grain boundary bonding strength decreased, crack propagation was not hindered by deflection, and the thermal shock cycle life, normal and high temperature strength, and anti-oxidation performance decreased.
[0125] In Comparative Example 4, the absence of ceramic precursor B resulted in the absence of a continuous spinel barrier layer at the magnesia-graphite interface, significantly increasing the contact area between the slag and periclase, accelerating the solid-phase melting reaction rate, and increasing the maximum erosion depth. The system also lacked some AlN high thermal conductivity particles, which reduced the internal thermal conductivity of the material, widened the cross-sectional temperature difference during thermal cycling, increased thermal stress, made cracks more likely to initiate prematurely, and reduced thermal shock stability and slag resistance.
[0126] In Comparative Example 5, both core modified ceramic precursors were eliminated, and the material relied solely on the traditional aluminum powder anti-oxidation system. Lacking the nitride oxygen barrier phase and the interface spinel anti-slag phase, the three damage pathways of oxygen diffusion, slag penetration, and thermal stress cracking were simultaneously aggravated, resulting in an increase in apparent porosity and a significant decrease in mechanical strength, anti-oxidation, anti-slag, and thermal shock performance.
[0127] After removing the precursor C in Comparative Example 6, no auxiliary sintering liquid phase was generated during the sintering process. The particle bonding was completed solely by solid-phase diffusion. The sintering necks between magnesia particles were not fully developed, and the open porosity of the material increased, becoming channels for oxygen and slag penetration. Without the role of liquid phase filling micropores and buffering thermal stress, the cracks continued to propagate during the hot and cold cycles and could not be alleviated. The thermal shock life, density, and slag resistance decreased simultaneously.
[0128] In Comparative Example 7, the excessive amount of precursor C resulted in the formation of an excessive silicate liquid phase during sintering, which continuously aggregated at the grain boundaries, replacing the direct grain bonding structure. The glass phase had low high-temperature stiffness and was prone to high-temperature creep, reducing its high-temperature flexural strength. The excessive liquid phase caused uneven cooling and shrinkage, resulting in grain boundary gaps. The Ca component in the liquid phase easily reacted with the ferrochrome slag to form a low-melting-point phase, promoting the penetration of slag along the grain boundaries.
[0129] Comparative Example 8: Ceramic precursor A was not pre-fired in nitrogen. The alloy powder and nano-chromium trioxide were only physically mixed. The nitriding reaction was not completely converted during the firing stage of the finished product, and a large amount of metal element remained. During high-temperature service, the metal element oxidized to generate discrete oxide particles, which increased the porosity of the matrix. The nitride reinforcement phase was insufficient, and the oxidation resistance and high-temperature mechanical strength decreased simultaneously.
[0130] In Comparative Example 9, ceramic precursor B was not pre-fired in segments. Nitrates and organic surfactants in the powder were concentrated and decomposed during the sintering stage of the finished product. A large amount of decomposition gas formed through-hole channels in the matrix, providing a path for oxygen and slag to penetrate. The spinel solid phase reaction could not be fully carried out, the amount of anti-slag protective phase generated at the interface was insufficient, and the anti-slag erosion and anti-oxidation performance was significantly reduced.
[0131] In Comparative Example 10, the precursor C was not pre-fired. Calcium and yttrium nitrates decomposed and released gases during the firing of the green body, leaving a large number of open pores in the matrix. The sintering densification effect was weakened, the apparent porosity increased, and the antioxidant, mechanical and thermal shock resistance properties deteriorated.
[0132] Comparative Example 11 was fired at a maximum temperature of only 500℃, resulting in incomplete carbonization of the thermosetting phenolic resin and an incomplete development of the continuous carbon bonding network. None of the three types of ceramic precursors reached the phase transformation temperature, making it impossible to generate nitride and spinel functional ceramic phases in situ. The material bonding strength was maintained solely by the incompletely carbonized resin. Under high-temperature conditions, the resin carbon was easily oxidized and lost rapidly, leading to a significant decrease in bonding strength and a marked deterioration in oxidation resistance.
Claims
1. A composite ceramic-modified magnesia-carbon refractory material, characterized in that, The raw materials include the following parts by weight: 60-70 parts of fused magnesia coarse aggregate, 15-20 parts of fused magnesia fine powder, 8-10 parts of ceramic precursor A, 6-8 parts of ceramic precursor B, 2-3 parts of precursor C, 10-12 parts of natural flake graphite, 0.2-0.6 parts of nano carbon black, 0.5-1 part of metallic aluminum powder, 3.8-5.0 parts of thermosetting phenolic resin, 0.2-0.4 parts of hexamethylenetetramine, and 1.8-3.5 parts of anhydrous ethanol.
2. The composite ceramic-modified magnesia-carbon refractory material according to claim 1, characterized in that, The ceramic precursor A is prepared by dispersing alloy powder, nano-chromium trioxide, and PEG400 in anhydrous ethanol at a mass ratio of 62-65:9-12:0.3-0.5, drying, and sintering at 650-700℃; the alloy powder is a mixture of iron powder, chromium powder, silicon powder, and nickel powder at a mass ratio of 100:20-22:10-12:3-5. The ceramic precursor B was prepared by stirring chromium nitrate nonahydrate, aluminum isopropoxide, tetrabutyl titanate, and PEG600 in a mixture of anhydrous ethanol and deionized water at a mass ratio of 22-26:24-28:5-7:1.5-2.5 to obtain a sol, which was then centrifuged, spray-dried, and sintered sequentially at 350-400℃ and 480-520℃. The precursor C is prepared by mixing calcium nitrate tetrahydrate, yttrium nitrate hexahydrate, boric acid, and tetraethyl orthosilicate in an ethanol-water solution at a mass ratio of 10–12:1.5–2:1.4–1.6:15–17, adjusting the pH to 2.2–2.8, stirring to obtain a sol, gelling, drying, pulverizing, sieving, and sintering in air at 580–620°C.
3. A composite ceramic-modified magnesia-carbon refractory material according to claim 1 or 2, characterized in that, The preparation method of the ceramic precursor A includes: mixing iron powder, chromium powder, silicon powder, and nickel powder in a mass ratio of 100:20-22:10-12:3-5 to obtain alloy powder; mixing alloy powder, nano-chromium trioxide, anhydrous ethanol, and PEG400 in a mass ratio of 62-65:9-12:150-200:0.3-0.5, dispersing evenly, and drying to obtain composite powder; sintering the composite powder at 650-700℃ for 1.5-2.5h under a high-purity nitrogen atmosphere; cooling, dispersing, and sieving to obtain ceramic precursor A.
4. The composite ceramic-modified magnesia-carbon refractory material according to claim 3, characterized in that, The iron powder, chromium powder, silicon powder, and nickel powder are all powders that have passed through a 300-325 mesh sieve; the D50 of the nano chromium trioxide is <200nm; the heating rate is 5-8℃ / min; and the sieving is done through a 300-325 mesh sieve.
5. A composite ceramic-modified magnesia-carbon refractory material according to claim 1 or 2, characterized in that, The preparation method of the ceramic precursor B includes: dissolving 22-26 parts by mass of chromium nitrate nonahydrate in a mixture of 45-50 parts by mass of anhydrous ethanol and 18-22 parts by mass of deionized water, and stirring to obtain a chromium salt solution; adding 24-28 parts by mass of aluminum isopropoxide to 55-60 parts by mass of anhydrous ethanol and stirring to obtain an aluminum isopropoxide ethanol suspension; adding the aluminum isopropoxide ethanol suspension dropwise to the chromium salt solution under a closed system at 60-65°C with stirring, and continuing to stir; adding 5-7 parts by mass of tetrabutyl titanate and continuing to stir; adding 1.5-2.5 parts by mass of PEG600 and continuing to stir to obtain a sol, centrifuging and spray drying to obtain precursor powder, sintering at 350-400°C for 3-3.5 h under a high-purity nitrogen atmosphere, then sintering at 480-520°C for 1.5-2 h, cooling, dispersing, and passing through a 300-325 sieve to obtain ceramic precursor B.
6. A composite ceramic-modified magnesia-carbon refractory material according to claim 1 or 2, characterized in that, The preparation method of the precursor C includes: dissolving 10-12 parts by mass of calcium nitrate tetrahydrate, 1.5-2 parts by mass of yttrium nitrate hexahydrate, and 1.4-1.6 parts by mass of boric acid in 90-95 parts by mass of 60-65 vol% ethanol aqueous solution, adjusting the pH to 2.2-2.8, and stirring until the solid is completely dissolved; adding 15-17 parts by mass of tetraethyl orthosilicate, stirring and hydrolyzing at 45-50℃ to obtain a homogeneous sol, and allowing it to stand in a sealed container to complete gelation; drying, pulverizing, and sieving to obtain powder; sintering the powder at 580-620℃ for 2-2.5 h in an air atmosphere, cooling, and ball milling to D50≤5μm to obtain precursor C.
7. The composite ceramic-modified magnesia-carbon refractory material according to claim 6, characterized in that, The pH is adjusted using 0.5–1.0 mol / L dilute nitric acid; the sealed standing is carried out at 58–62°C for 12–16 hours to complete gelation; the sieving is carried out through a 200–250 mesh sieve.
8. The composite ceramic-modified magnesia-carbon refractory material according to claim 1, characterized in that, The particle size distribution of the fused magnesia coarse aggregate is as follows: the mass ratio of 5mm ≥ particle size > 3mm, 3mm ≥ particle size > 1mm, and 1mm ≥ particle size > 0.074mm is 0.8~1.2:1.0~1.3:0.4~0.7; the D50 of the fused magnesia fine powder is 40~70μm; the particle size of the natural flake graphite is ≤0.15mm; the D50 of the nano carbon black is 50~80nm; the D50 of the aluminum powder is 1~5μm; the thermosetting phenolic resin is a liquid thermosetting phenolic resin with a viscosity of 20~30Pa·s at 25℃, a solid content of ≥75wt% at 180℃, and a residual carbon content of ≥43wt% after calcination at 800℃ for 7min.
9. The method for preparing a composite ceramic-modified magnesium-carbon refractory material according to claim 1, characterized in that, Includes the following steps: S1: Premix fused magnesia fine powder, nano carbon black and metallic aluminum powder evenly to obtain premixed fine powder; S2: The fused magnesia coarse aggregate is premixed evenly, natural flake graphite is added and mixed evenly, then anhydrous ethanol is added and mixed evenly, ceramic precursor A, ceramic precursor B, precursor C and premixed fine powder are added in sequence and mixed evenly, and finally thermosetting phenolic resin and hexamethylenetetramine are added and mixed evenly to obtain mud and bridging material. S3: The clay is poured into the mold and pressed into shape. The density of the formed blank is controlled between 2.98 and 3.08 g / cm³. 3 ; S4: Under the protection of high-purity nitrogen, the formed green body is sintered at 120-150℃ for 6-8 hours at a rate of 1-2℃ / min; then sintered at 200-250℃ for 10-12 hours at a rate of 1-2℃ / min; then sintered at 300-350℃ for 6-8 hours at a rate of 2-3℃ / min; then sintered at 800-850℃ for 3-5 hours at a rate of 2-3℃ / min; then cooled and removed from the furnace to obtain the formed refractory product.
10. The method for preparing a composite ceramic-modified magnesia-carbon refractory material according to claim 9, characterized in that, In S2, the mixing control temperature is below 45℃; the acclimated material is mud placed in a sealed environment at 23-28℃ and relative humidity of 40-60% for 20-24 hours; in S3, the pressing pressure is 85-135MPa; in S4, the cooling rate is: below 2℃ / min to 350-400℃, and below 3℃ / min to 30-60℃.